Exploring small-scale direct air capture in a building ventilation system: a case study in Linköping, Sweden - Milić, Vlatko; Larsson Ståhl, Andreas; Granli, Axel; Moshfegh, Bahram (Frontiers in Energy Research, 2024)
Direct Air Capture (DAC) technologies have emerged as a promising solution to address climate change and meet global climate goals. However, despite the importance of DAC in designing carbon-negative buildings, there is a lack of research focusing on the energy and cost aspects in building ventilation systems. The objective of this research is to investigate the CO2 capture potential and economic viability of integrating small-scale DAC into a building ventilation system integrated within a gym space. A gym space located in the city of Linköping, Sweden, is used as the research object. Furthermore, the study investigates the CO2 capture potential across a portfolio of gym spaces corresponding to an area of 24,760 m2. The results show that the CO2 capture potential varies between 54 kg/day and 83 kg/day for the investigated gym space. Moreover, the total CO2 capture potential is between 588 ton CO2/year and 750 ton CO2/year for the portfolio of gym spaces. The results also demonstrate that regenerating the sorbent during non-operating hours is more energy-efficient and economically advantageous compared to performing four complete regeneration cycles during operating hours. Based on a sorbent capture potential of 0.2 mmol/g and 2.0 mmol/g, and a CO2 price of 1,000 SEK, the break-even price for energy is 0.25–0.53 SEK/kWh. Lastly, the research shows that, among the investigated cases, the only economically viable solution corresponds to sorbent capture potential 2.0 mmol/g and utilizing low-grade heat for the generation process, resulting in a total cost of 663 SEK/ton CO2.